Manajemen Program Adiwiyata Dalam Membentuk Karakter Peduli Lingkungan Bagi Siswa MTs Negeri 3 Ponorogo - Fifi Dwi Novitasari; Athok Fu'adi (Edumanagerial, 2023)
The background of this research is the accumulation of waste at MTs Negeri 3 Ponorogo and wanting to change the character of students who care about the environment. The character of caring for the environment can be formed in various ways, one of which is through the implementation of the Adiwiyata program. This program will impact generations of people who respect their environment more. MTs Negeri 3 Ponorogo has implemented and won a provincial level award as an Adiwiyata madrasah. This study aims to describe and analyze the implementation of the Adiwiyata program management in shaping the character of caring for the environment for students at MTs Negeri 3 Ponorogo starting from planning, implementing, and evaluating. This research is field research with a qualitative approach. The data source was obtained from informants directly related to the thesis discussion—data collection techniques by conducting interviews, observation, and documentation. From the results of this study, it can be concluded that: (1) The planning of the Adiwiyata program in shaping the character of caring for the environment for MTs Negeri 3 Ponorogo students is by planning environmentally sound activities, such as clean Friday activities, waste management, class pickets, inter-class competitions. (2) The implementation of the Adiwiyata program in shaping the character of caring for the environment for students of MTs Negeri 3 Ponorogo, namely through the three principles and components of the Adiwiyata program. (3) Evaluation of the Adiwiyata program in shaping the character of caring for the environment for MTs Negeri 3 Ponorogo students, namely from the attitudes and behavior of students in their daily activities, an evaluation is carried out with the working group team for once a month and for the Adiwiyata team it is carried out once a year.